PENGARUH E-SERVICE QUALITY TERHADAP E-SATISFACTION PENGGUNA APLIKASI TOKOPEDIA ( STUDI KASUS PADA MAHASISWA STIA MALANG) - Maria Paskalia; Tri Marhaeni Widiastuti (STIA MALANG, 2022)
This study was conducted by researchers to analyze the effect of E-service quality on E-Satisfaction ofstudents using the Tokopedia application at the College of Administrative Sciences (STIA) Malang, E-servicequality is the quality of electronic services that can support E-Satisfaction or from consumer perceptions. ononline convenience, trade/transaction methods, site design, and services. Maximum e-service quality from acompany is very useful for increasing the e-satisfcation of its users. This is the background for researchers toexamine the effect of e-service quality on e-satisfaction of students using the Tokopedia application at the Collegeof Administrative Sciences (STIA) Malang.This research is a type of quantitative research using descriptive research methods. The population of thestudy was all students at the College of Administrative Sciences (STIA) Malang users of the Tokopedia applicationwith a total sample of 120. This study used simple random sampling with data collection methods by distributingquestionnaires or questionnaires through google form and analyzing data using linear regression analysis. simplewith the help of SPSS application. The results of this study, the total mean e-service quality is 4.50 and is included in the high category, thetotal mean e-satisfaction is 4.48 and is in the high category. Hypothesis test with a value of 10.712 > 1.65787 (thevalue of t table) so that it is proven that there is an effect of e-service quality on e-satisfaction. The results of theregression analysis show that the regression coefficient value is positive + 0.550 which means that theindependent variable (e-service quality) has a positive effect on the dependent variable (e-satisfaction). Then thevalue of the coefficient of determination (R^2) is 0.503 . Thus, it can be concluded that the hypothesis of the eservice quality variable has a significant positive effect of 50.3% on e-satisfaction. Researchers suggest for theTokopedia application, even though all indicators in the variables are in good category, it would be nice if theTokopedia application continues to improve the quality of its services in the field of adding attractive promos andfacilitating the flow of refunds, because if the e-service quality of the Tokopedia application increases it willincrease e-commerce’s user satisfaction.Keywords: E-service quality, E-Satisfaction, Tokopedia, STIA Malang student